2021
DOI: 10.32541/recie.2021.v5i2.pp81-91
|View full text |Cite
|
Sign up to set email alerts
|

Variables predictoras de la expectativa de desempeño y la intención de abandono en contexto de educación virtual de emergencia en estudiantes universitarios chilenos

Abstract: El actual contexto de educación virtual de emergencia producto de la pandemia del COVID19 ha traído nuevas condiciones al escenario educativo. En este contexto, esta investigación busca evaluar la capacidad predictiva de las expectativas de compromiso, el apoyo social, la calidad y dominio de los recursos informáticos, las Notas de Enseñanza Media (NEM) y el puntaje obtenido en la Prueba de Selección Universitaria (PSU) sobre las expectativas de desempeño y la intención de abandono durante el primer semestre a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 13 publications
1
6
0
1
Order By: Relevance
“…On the other hand, when students do not feel valued and respected by others, or do not feel that they belong to a social environment, they are more likely to drop out of their studies [72], the sense of belonging to the career being a significant predictor of the dropout intention in university students [73].…”
Section: Sense Of Belongingmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, when students do not feel valued and respected by others, or do not feel that they belong to a social environment, they are more likely to drop out of their studies [72], the sense of belonging to the career being a significant predictor of the dropout intention in university students [73].…”
Section: Sense Of Belongingmentioning
confidence: 99%
“…It has been observed that high levels in the sense of belonging in university students contribute to increasing their levels of participation, being able to seek help in the face of difficulties, feeling less alone, anxious, or depressed, increasing the use of self-regulation strategies, and raising levels of academic self-confidence and motivation [64,66,77]. In addition, various investigations have observed that the sense of belonging turns out to be a direct predictor of study engagement, dropout, and permanence in studies [40,41,45,65,66,73,[77][78][79][80].…”
Section: Sense Of Belongingmentioning
confidence: 99%
See 3 more Smart Citations